The Growth of Oil Palm Seedlings using a Combination Medium of Organic Oil Palm Empty Fruit Bunch and NPK Fertilizer at Main Nursery - Hapsoh Hapsoh; Isna Rahma Dini; Wawan Wawan; Astri Helga Sianipar (JOURNAL OF TROPICAL SOILS, 2020)
Oil palm (Elaeis guineensis Jacq.) holds a very strategic role in the Indonesia economy. Plants that have reached the economical age of 25 years need to be replanted using qualified oil palm seedling. The qualified seedling is obtained through proper fertilization. The combination of NPK fertilizer and organic material of oil palm empty fruit bunches (OPEFB) which has been given a cellulolytic bacterial consortium can provide sufficient nutrients for the growth of oil palm seedlings. The study aimed to determine the effect of giving a combination of OPEFB organic material, cellulolytic bacterial consortium, and NPK fertilizer on the growth of oil palm seedling (Elaeis guineensis Jacq.) at main nursery. This experiment used a single factor experiment arranged in a Completely Randomized Design (CRD). The treatments were a 100% NPK, a OPEFB compost, a 50% NPK + OPEFB compost, a 50% NPK + OPEFB + Cellulolytic bacterial consortium, and a OPEFB + cellulolytic bacterial consortium. The results showed that the application of inorganic fertilizers combined with organic fertilizers (a OPEFB compost and a OPEFB + cellulolytic bacterial consortium) had a good effect on each parameter. Giving organic fertilizer without inorganic fertilizer had not affected plant growth on all parameters. Application of a OPEFB compost and a OPEFB + cellulolytic bacterial consortium can reduce the use of inorganic fertilizers by 50%.